Association between emotional intelligence and academic performance among students in Gandaki Medical College, Pokhara - Shrestha, Rami; Shrestha, Nirmala; Koju, Sapana; Tako, Ratna Keshari (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: Recent studies in last few decades are revealing that Intelligence Quotient (IQ) alone is not a reliable factor of students’ academic achievement. It has been claimed that only 20% of a person’s success can be attributed to IQ and rest 80% to Emotional Quotient. Since, many researchers had claimed the influence of emotional intelligence on academic performance; the aims of this study were to find out the level of emotional intelligence and its relation with academic performance among Nepali undergraduate students.Methods: A cross sectional study was carried out in 280 medical students (120 male, 160 female). The data of this research was obtained through the use of a questionnaire which elicits information about their Emotional Intelligence level and academic performance. The obtained data was analyzed by SPSS. The degree of relationship between marks obtained and emotional intelligence were established by Correlation coefficient and Fischer exact test. The level of significance was set at p-value less than 0.05.Results: The mean level of emotional intelligence was high (5.055±0.798) among Nepalese medical students. The respondents were reported to have high level of emotional intelligence with (5.544±0.929) for Self- awareness, (5.035±1.01) for Social awareness, (5.394±1.11) for Social skill and moderate level of emotional intelligence (4.24±1.37) for Self-management.Conclusion: There was a positive and strong relationship between the respondents’ overall emotional intelligence and their academic achievement which means that the higher their level of emotional intelligence, the better they perform academically.